Microbial populations, sensory, and volatile compounds profiling of local cooked rice - Nur-Shahera, Mohammad Sabri; Nor Ainy, Mahyudin; Muhammad Shirwan, Abdullah Sani; Han, Ming Gan *; Chong, Kah Hui; Padmanabhan, Kousalya; Shan, Jiang; Nor Khaizura, Mahmub Ab Rashid (Oxford University Press, 2024)
Objectives This study is designed to investigate the microbial populations, sensory, and volatile compounds profiling of locally cooked rice stored at room temperature (30 °C) on days 0, 1, 2, and 3 (D0, D1, D2, and D3) for the determination of specific spoilage organisms (SSOs).